Edukatif Socialization of Basic International Trade Education Management for Children at Berkat Bintang Sejati Indonesia Orphanage Through Interactive Learning and Educational Games: Indonesia - Hengky Kosasih; Elyzabeth Wijaya; Susanto; Jeslyn; Jerischo (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2026)
This study examines the implementation of a Community Service Program (PKM) entitled “Edukatif Socialization of Basic International Trade Education Management for Children at Berkat Bintang Sejati Indonesia Orphanage Through Interactive Learning and Educational Games.” The program aims to introduce fundamental concepts of international trade to orphanage children while fostering their cognitive, social, and entrepreneurial skills. The activities are designed to provide basic knowledge on topics such as export-import processes, global markets, simple trading mechanisms, and the role of international business in economic development. To enhance learning effectiveness, the program adopts interactive teaching methods, including simulations, role-playing, and educational games, allowing participants to actively engage and better understand abstract economic concepts. In addition, the program emphasizes the development of soft skills such as communication, teamwork, problem-solving, and critical thinking. Through participatory learning approaches, the children are encouraged to explore their creativity and build confidence in understanding global economic activities. The effectiveness of the program is evaluated based on participants’ ability to comprehend basic trade concepts and actively participate in simulation activities, supported by feedback from facilitators and participants. The findings indicate that interactive and game-based learning methods are highly effective in delivering foundational knowledge of international trade, while also contributing to the empowerment and future readiness of orphanage children.